Annual Report on Exchange Arrangements and Exchange Restrictions 2013. (Annual Report on Exchange Arrangements and Exchange Restrictions, 2013)
This is the 64th issue of the AREAER. It provides a description of the foreign exchange arrangements, exchange and trade systems, and capital controls of all IMF member countries. It also provides information on the operation of foreign exchange markets and controls on international trade. It describes controls on capital transactions and measures implemented in the financial sector, including prudential measures. In addition, it reports on exchange measures imposed by member countries for security reasons. A single table provides a snapshot of the exchange and trade systems of all IMF member countries. The Overview describes in detail how the general trend toward foreign exchange liberalization continued during 2012, alongside a strengthening of the financial sector regulatory framework. The AREAER is available in several formats. The Overview in print and online, and the detailed information for each of the 191 member countries and territories is included on a CD that accompanies the printed Overview and in an online database, AREAER Online. In addition to the information on the exchange and trade system of IMF member countries in 2012, AREAER Online contains historical data published in previous issues of the AREAER. It is searchable by year, country, and category of measure and allows cross country comparisons for time series.